Technical Advancement in the Design of Interior Spaces for the Disabled - Yasir Kareem Hassan; Nrmeen Wameed Ahmad (Journal of Techniques)
Technical upgrading is a transitional stage in the development of interior spaces whose importance has emerged in the current era، and technical development is one of the important matters whose features have become clear in many interior spaces، and it is necessary to take advantage of these developments within the needs of society and upgrade what is appropriate for them، as some need The interior spaces are upgrading and developing in their designs within the needs of society and attention in some groups، especially people with disabilities، because many people with mobility disabilities need the help of others within the limits of their living and university environment، especially in the process of walking، climbing stairs، movement activities inside the classrooms and when going out and other necessary needs. Therefore، the research problem came in the following question: How do we achieve technical upgrading in the design of disabled movement paths within university educational spaces? The research aims to reveal the mechanisms and requirements of technical upgrading in the design of interior spaces for the disabled. For the disabled، as for the spatial limit of the interior spaces of educational buildings (universities) in Turkey_Istanbul with the temporal limit for the year 2010_2013. While the theoretical framework included (technical advancement in the design of interior spaces) and (designs of interior spaces for the disabled)، the research procedures represented in the research methodology based on the descriptive approach in analyzing the sample models. The research community relied on the intentional selective method، and the sample was 20% of the population. The research and the research tool used was the analysis form، and the validity of the used tool was verified، as the analysis axes form was presented to a group of experts with specialization، as the ratio of the reliability coefficient reached 91%. The interior space depends on the design of ramps inside the spaces، which is one of the alternative means of transporting wheelchair users to move from one level to another، relying on fixing (the armrest) to protect and reduce risks. The chapter also presented recommendations and suggestions.